Pengaruh Rasio Return On Asset & Return On Equity terhadap Harga Saham Perusahaan Sub Sektor Perkebunan di Bursa Efek Indonesia Periode 2016-2020 - Ahmad Rhozikin (Universitas Batanghari Jambi, 2021)
The purpose of this study is to find out and analyze how the effect of return on asset ratio (ROA) and return on equity ratio (ROE) simultaneously on stock prices in Plantation Sub-Sector Companies for the Period 2016-2020. To find out and analyze how the effect of return on asset ratio (ROA) and return on equity ratio (ROE) partially on the stock price in Plantation Sub-Sector Companies for the Period 2016-2020. In this research design is a descriptive design that is a study that is an exposure to the variables studied and the dependence of sub-variables. In this study the study using descriptive design involves quantitative data equipped with qualitative data. The object of the research used in this study is the plantation industry listed on the Indonesia Stock Exchange (IDX). The reason the author uses the plantation industry as an object of research is because in Indonesia Plantation has a very wide market share which is one of the largest foreign exchange distributors for the country so that it can provide a significant role for the Indonesian economy. From the values of the coefficient obtained the following linear regression equation: Log Y = 3,966 + 2,403 X1 – 2,580 X2 + e. The regression coefficient of the return on asset (X1) variable of 2,403 means that the return on asset (X1) has a positive effect on the stock price. This indicates that if the return on asset (X1) increases by 1%, then the stock price will increase by 2,403.The value of the variable regression coefficient of return on equity (X2) 2,580 gives the sense that the return on equity (X2) negatively affects the stock price. This indicates that if the return on equity (X2) increases by 1%, then the stock price decreases by 2,580%. Simultaneously return on asset and return on equity have a significant effect on the stock price of 0.425 this figure shows that variable return on asset (X1) and return on equity (X2) can explain the change in stock price profit of 42.5 instead of 57.5% caused by other variables outside of this study.